Butler, Judith (2021), A força da não-violência - Fidalgo, Pedro (2022)
Recensão de: Butler, Judith (2021), A força da não-violência. Lisboa: Edições 70, 166 pp. Tradução de Hugo Barros [ed. orig. 2020]